Analysis of the efficacy of avatrombopag for the delayed platelet engraftment after allogeneic hematopoietic stem cell transplantation for aplastic anemia - Zhang, Xinhe; Feng, Jia; Tan, Zhengwei; Zhang, Herui; Hu, Huijin; Zhao, Yuechao; Wu, Dijiong; Zhang, Yu; Wu, Liqiang; Hu, Tonglin; Yan, Zhengsong; Ye, Baodong; et al. (Frontiers in Medicine, 2025)
BackgroundDelayed platelet engraftment (DPE) after allo-HSCT lacks standard therapy. Avatrombopag (AVA), a second-generation TPO agonist, is often delayed until transfusion-related events occur, potentially harming high-risk recipients.ObjectivesWe compared recombinant human thrombopoietin (rh-TPO) with early AVA switching for treating DPE in aplastic anemia (AA) patients post-allo-HSCT to optimize management strategies.MethodsThis single-center study retrospectively enrolled 154 consecutive AA patients receiving allo-HSCT at Zhejiang Provincial Hospital of Traditional Chinese Medicine (March 2019–September 2023). Of these, 39 deemed high-risk for poor platelet engraftment (advanced donor/recipient age, low CD34 + dose, etc.) were non-randomly assigned: (1) AVA group (n = 11), switched to avatrombopag if platelets remained <30 × 109/L on day +14 or <50 × 109/L on day +21; (2) rh-TPO group (n = 28), continued rh-TPO monotherapy. Allocation followed clinician judgment and patient consent.ResultsOur findings revealed that the 1-year overall survival (OS) rate was notably higher in AVA group (100% vs. 78.6%, p = 0.106). And the complete remission (CR) rate in the AVA group was significantly higher than that in the rh-TPO group at 3 and 6 months after transplantation(100% vs. 67.9%, p = 0.032; 100% vs. 71.4%, p = 0.047). At 3 months post transplantation, the platelet engraftment rate in the AVA group was significantly higher than that in the rhTPO group (67.9% vs. 100%, p = 0.04). The median time to achieve platelet engraftment was 20 (13, 25) days for the AVA group and 23 (10, 68) days for the rh-TPO group. Additionally, the AVA group reached platelet counts of 30, 50, and 125 × 109/L more rapidly than the rh-TPO group. Furthermore, at 3 months post-transplantation, the median platelet transfusion volume of AVA group was less than rh-TPO group (63 U vs. 82 U, p = 0.141).ConclusionFor patients identified as being at high risk for poor platelet engraftment following allo-HSCT, early transition to AVA can significantly reduce the duration of DPE and promote platelet recovery post-transplantation. This strategy has the potential to enhance patient survival rates and overall outcomes.